The relationship between job crafting and job performance and the mediating effects of job satisfaction: A study on warehouse worker in Bukit Kayu Hitam, Kedah Malaysia - Noraziela, Abdul Razak (2014)
This work aims to examine the relationship between job crafting and job performance. It also aims to test the mediating role of job satisfaction in these relationships. Warehouse worker in Bukit Kayu Hitam, Malaysia was a respondent. Data was collected through a questionnaire survey of 120 respondents using the approach of quantitative research methods. A total number of 120 respondents were given questionnaires to fill but only 84 questionnaires were retrieved back for analysis. The overall findings indicated that there are relationships between job crafting and job performance. The result suggested that there is a significant and positive relationship. Moreover, it was also found that job satisfaction was partially mediated the relationships between job crafting and job performance. This study is limited in term of sample size. Therefore, future researches should choose the larger population so that sample size can be bigger. Employee job performance is important towards the organization operation. Employee should be given opportunity to improve their job performance and one of the ways was through job crafting. Job crafting not only can increase job satisfaction but also can increase job performance.